EFEKTIVITAS METODE JIGSAW BERBASIS CULTURALLY RESPONSIVE TEACHING (CRT) TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATERI HIDROLISIS GARAM - Gusman, Tania Avianda; Alyanza, Yurika Angellina; Salsabila, Tahara; Vernando, Vigo; Saroah, Saroah (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the improvement in students' learning outcomes on the topic of Salt Hydrolysis through the implementation of the Cooperative Learning model of the Jigsaw type integrated with the Culturally Responsive Teaching (CRT) approach. The material focus includes pH calculations of three types of salts: salts resulting from the reaction of a strong acid with a weak base, a weak acid with a strong base, and a weak acid with a weak base. This topic was selected because it requires a deep conceptual understanding and mastery of calculation skills, which are often challenging for students in chemistry learning. The CRT approach was employed to connect the learning material with students' cultural contexts and needs, making the learning process more meaningful and contextual. This study used a quantitative analysis method by measuring the N-Gain scores based on pre-test and post-test results administered to 35 students of class XI.11 at SMAN 1 Sumber. The results showed that the implementation of the Jigsaw method led to a learning improvement of 90.57 and a mastery level of 77% among the students